Investigating the influence of internet usage on income inequality in transitional countries: Array - Tsaurai, Kunofiwa; Chimbo, Bester (EuroEconomica, 2021)
The study investigated the impact of internet usage on income inequality in transitional economies using panel data ranging from 2008 to 2019. The second objective was to find out the influence of the complementarity between internet usage and human capital development on income inequality in transitional economies using the same data set. The available literature on the subject matter is divergent, conflicting, and far from reaching a consensus, hence the reason why the author attempted to empirically investigate the impact of internet usage on income inequality. The lag of income inequality was found to have had a significant positive influence on income inequality under the dynamic generalized methods of moments (GMM). Fixed effects produced results which show that internet usage had a significant negative effect on income inequality, consistent with the available literature. Transitional economies are therefore urged to develop and implement policies that promotes a wide coverage of internet usage to reduce income inequality. The interaction between internet usage and human capital development was found to have had a significant positive impact on income inequality under the fixed effects whilst pooled ordinary least squares (OLS) shows that the impact of the complementarity between internet usage and human capital development on income inequality was negative but significant. Transitional economies are therefore urged to implement enhanced human capital development policies to enable internet usage to play a meaningful role in reducing income inequality in the society. Future research needs to establish minimum threshold levels that internet usage in transitional economies must reach to have a significant influence on income inequality. Such a study enriches the income inequality policy making and implementation programmes.